Implementation of LPP TVRI Riau's Analog Switch-Off (ASO) Migration in Welcome to the Digitalization of Indonesian Broadcasting - Abdullah Mitrin; Rudi Rahman; N. Doni Dwi Putra (International Journal of Advance Social Sciences and Education (IJASSE), 2023)
After the birth of Law Number 11 of 2022 concerning Job Creation which has added one article to Law Number 32 of 2002 concerning Broadcasting, it requires broadcasters to switch from analog technology to digital technology or Analogue switch-off (ASO) no later than two years from the law was passed. Considering that the deadline for the Broadcasting Institution's Analogue Switch Off (ASO) is November 2, 2022, this is a serious problem for the TVRI Public Broadcasting Institution, especially the Riau station, which is the leading sector for the national analog switch-off (ASO) program for all TV stations. This research aims to look at the implementation of regulations and obstacles in the process of implementing the LPP TVRI Riau Analogue Switch-Off (ASO) migration in welcoming the digitalization of Indonesian broadcasting. The research method was carried out qualitatively, namely in-depth interviews, observation and document review for the Implementation of LPP TVRI Riau Analog Switch Off (ASO) Migration in Facing the Digitalization of Indonesian Broadcasting. TVRI Riau prepares new human resources and regular training policies, regularly socializes government policies regarding the digitalization of broadcasting in the internal broadcast media line, and provides education to the public that ASO requires the public to have additional Set Top Box (STB) equipment. TVRI Riau has now implemented full digital broadcasts, only the broadcast duration is still the same as analog. As the organizer of Mux TVRI Riau which has 4 channel slots, namely national TVRI, TVRI Sport, TVRI Word and local TVRI.